Predictors of virologic failure and genotypic resistance mutation patterns in thai children receiving non-nucleoside reverse transcriptase inhibitor-based antiretroviral Therapy - Podjanee Jittamala (2018)
Background: Nonnucleoside reverse transcription inhibitor (NNRTI)-based antiretroviral therapy (ART) has been widely used as a first-line regimen for the treatment of HIV. This study aimed to determine the rate and predictors of virologic failure and describe patterns of resistance mutation. Methods: The inclusion criteria were children who were <18 years and receiving NNRTI-based ART. Plasma HIV-1 RNA and CD4 were monitored every 6 months. Virologic failure was defined as plasma HIVRNA >1000 copies/mL. Results: Forty (20%) of 202 children had virologic failure, of whom 33 (16%) failed in the first year of therapy. By multivariate analysis, the children who received nevirapine were 3.7 times more likely to develop virologic failure than those receiving efavirenz (P = 0.006). The prevalence's of patients with-1 major mutations conferring drug resistance to nucleoside reverse transcription inhibitors (NRTIs) and NNRTIs were 89% and 97%, respectively. The common NNRTI mutations were Y181C/I (58%) and K103N (34%). The NRTI mutations were M184V/I (84%), K65R (11%), Q151M (5%), and-3 TAMs (3%). Conclusions: The virologic failure rate in children was high and mostly occurred in the first year of treatment. The most common resistance mutations were those conferring resistance to NNRTIs and lamivudine. There were few instances of multiNRTI resistance. Early detection of virologic failure might allow more options for second-line regimens. Copyright © 2009 by Lippincott Williams and Wilkins.